Potensi Ekstrak Etanol Clitoria ternatea L. sebagai Biofungisida dalam Mengendalikan Jamur Fusarium sp. - Irna Il Sanuriza; Dwi Kartika Risfianty; Irfan Jayadi; Mia Afrianti (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2021)
Fusarium sp is a fungal pathogen that can infect plants with a wide host range. Fusarium question is a type of pathogen from a group of fungi that has a high level of virulence so that it can cause high damage to plants. Biological control of soil-borne diseases by utilizing extracts from plants as an alternative barrier to avoid the use of synthetic chemicals. Plants used as control or inhibitors of the growth of the fungus Fusarium sp., have compounds in the form of triterpenoids, flavonoids, tannins, essential oils, and allelopathic compounds that are released to inhibit the growth of pathogens. This research is descriptive using the literature study method to find out the potential of plant extracts that have inhibitory power on the growth of the fungus Fusarium sp. The results of the potential study of this plant extract showed that the ethanolic extract of Clitoria ternatea L. had an effect on inhibiting the growth of the fungus Fusarium sp.